Genetic gain through progeny testing vs MOET in Murrah herds of various sizes - GANDHI, R S; SINGH, AVTAR (The Indian Journal of Animal Sciences, 2013)
Expected genetic gains in milk production from different mating schemes in small, medium and large herds of Murrah buffaloes were compared. The expected genetic gain(expressed as per cent of herd mean) from progeny testing, progeny testing supplemented by MOET (hybrid or milied MOET), hybrid MOET with use of a few bulls,juvenile MOET and adull MOET were 1.02, 1.19. 1.35, 1.66 and 1.73, respectively, from small population (N=400); 1.08, 1.25, 1.43,2.02 and 2.16, respectively, from medium population (N=2000); and 1.34, 1.51, 1.74, 2.20 and 2.37, respectively, from large population (N= 10,000). The superiority of adult MOET in comparison to progeny testing in terms of enhancing theoretical genetic gain for small, medium and large populations was 70.07,100 and 77.47% respectively. In comparison to small herd size, the per cent increase in expected genetic gain in medium and large herds from different mating schemes were; 6.08 and 31.11 % under progeny testing, 5.11 and 26.55% under hybrid MOET, 5.55 and 28.40% under hybrid MOET with a few bulls, 22.13 and 32.75% under juvenile MOET and 24.93 and 36.81 % under adult MOET. It was concluded that medium-sized population was best to obtain maximum genetic gain (2 times of progeny testing) from adult MOET.